2022
DOI: 10.1101/2022.05.25.493080
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

γ-Protocadherins control synapse formation and peripheral branching of touch sensory neurons

Abstract: SummaryLight touch sensation begins with activation of low-threshold mechanoreceptor (LTMR) endings in the skin and propagation of their signals to the spinal cord and brainstem. We found that the clustered protocadherin gamma (Pcdhg) gene locus, which encodes 22 cell-surface homophilic binding proteins, is required in somatosensory neurons for normal behavioral reactivity to a range of tactile stimuli. Developmentally, distinct Pcdhg isoforms mediate LTMR synapse formation through neuron-neuron interactions a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 125 publications
3
11
0
Order By: Relevance
“…This finding was confirmed using a series of vibration steps of increasing amplitudes again demonstrating decreased firing in response to 25 Hz vibration stimuli (Figure 6C). Thus, the functional deficits in RA-LTMRs correlate well with the defects in LTMR cutaneous projections we observed in Isl1 Interestingly, Meis2 inactivation seems to interfere with the embryonic expression of many members of the protocadherin family, and the protocadherin γ cluster (Pcdhg) in particular has recently been highlighted as essential for building central and peripheral LTMRs innervation and synapses and establish proper peripheral target-field innervation and touch sensation (23).…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…This finding was confirmed using a series of vibration steps of increasing amplitudes again demonstrating decreased firing in response to 25 Hz vibration stimuli (Figure 6C). Thus, the functional deficits in RA-LTMRs correlate well with the defects in LTMR cutaneous projections we observed in Isl1 Interestingly, Meis2 inactivation seems to interfere with the embryonic expression of many members of the protocadherin family, and the protocadherin γ cluster (Pcdhg) in particular has recently been highlighted as essential for building central and peripheral LTMRs innervation and synapses and establish proper peripheral target-field innervation and touch sensation (23).…”
Section: Introductionsupporting
confidence: 71%
“…Thus, the gene list associated with the GOterm “synapse” strongly links LTMR neurotransmitter type of synapses, their dysfunction in mouse model of ASD ( 24 , 25 ) and the association of Meis2 with ASD ( 26 , 65 , 74 ). Interestingly, Meis2 inactivation seems to interfere with the embryonic expression of many members of the protocadherin family, and the protocadherin γ cluster (Pcdhg) in particular has recently been highlighted as essential for building central and peripheral LTMRs innervation and synapses and establish proper peripheral target-field innervation and touch sensation ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, recent work has shown that the GPI-linked receptor Netrin-G1 is required in LTMRs for the proper maturation of terminal endings around hair follicles, but not for terminal axon branching or receptive field size (Meltzer et al, 2022b preprint). In contrast, ɣ-Protocadherins are important for the peripheral branching and innervation of non-guard hair follicles by Aβ-LTMRs, but not for the maturation of LLEs (Meltzer et al, 2022a preprint). Together, these data suggest that the initial innervation of hair follicles and the morphological maturation of their terminal endings are distinct events regulated by different molecular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these data suggest that the initial innervation of hair follicles and the morphological maturation of their terminal endings are distinct events regulated by different molecular pathways. Interestingly, terminal Schwann cells are the source for ligands/binding partners for both Netrin-G1 and ɣ-Protocadherins in LTMRs, demonstrating that they play a critical role in regulating hair follicle innervation (Meltzer et al, 2022a preprint; Meltzer et al, 2022b preprint).…”
Section: Discussionmentioning
confidence: 99%